Evaluación en la implementación de buenas prácticas de manufactura para chocolate en la microempresa “Seva” de Tosagua - García Vélez, Juana Valentina (2021)
The objective of this research was to evaluate the implementation of Good Manufacturing Practices to ensure the safety of chocolate at the "SEVA" microenterprise in Tosagua. An operational analysis and selection of the appropriate technology to ensure the safety of the chocolate was applied, and a checklist was used to verify the state of the infrastructure and the way of working within the microenterprise. To evaluate the safety of the chocolate, 18 random samples were taken from the same batch, based on INEN 537 regulations. Subsequently, Microbiological analyses of Salmonella, molds and yeast, total coliforms, E. coli and mesophilic aerobes were carried out prior to the implementation of the GMP Manual, after this the data obtained in the checklist were tabulated in the Excel 2013 program, where an initial compliance of 46% and a non-compliance of 54% were identified. Undoubtedly, the application of the operational analysis in the chocolate manufacturing process allowed the improvement of several operations in which setbacks were present and contributed to the implementation of the GMP manual, in addition to suggesting the appropriate technology needed within the microenterprise. To prove the benefits of the techniques applied in this research, a post-diagnosis of the requirements was carried out, meeting 76% of the requirements, demonstrating that the implementation of the GMP manual had a positive impact on the assurance of chocolate safety.